Frasa Bahasa Bali Kuna dan Perkembangannya ke Bahasa Bali Modern - Ni Luh Sutjiati Beratha (Pusat Kajian Bali Universitas Udayana, 2012)
AbstractThe Balinese language is the language is only known fromBalinese inscriptions dated to 882 – 1050 AD, then evolvedto Modern Balinese. This article discusses about Old Balinesephrases and their development to Modern Balinese,i.e. by explaining the structure or word order of the phrases.The Old and Modern Balinese phrases will be analysedby applying a theory of structural linguistic typologywhich is developed by Greenberg, while the analysis of theinternal structure of the phrases uses sub-theory of Governmentand Binding (GB) which developed by Chomskyand his followers, particularly X-bar theory. The claim ofthis theory is a phrase always has a head from the samecategory of a phrase as a whole, and this means that thestructure of phrases is always endocentric. Formation roleof a phrase is projected from lexicon and in this article theanalysis will be presented using a tree diagram.It appears that the Old Balinese and Modern Balinesephrases are endocentric, consisted of noun phrases, verbphrases, adjective phrases, and prepositional phrases whichtheir head are nouns, verbs, adjectives, and prepositions.It is interesting to note that in its development (from OldBalinese to Modern Balinese), there are innovations orsome changes have taken place from Old Balinese phrasesto Modern Balinese phrases. Innovations in word orderchange consisted of reversal of word order, simplificationor reduction, and elaboration. These innovations areinternal and regular.